RESOLUSI KONFLIK KEAGAMAAN BERBASIS KEARIFAN LOKAL: STUDI ATAS PELA GANDONG DI AMBON - Ismail, Roni; Wakano, Abidin; Leasiwal, Genoveva (Living Islam: Journal of Islamic Discourses, 2022)
AbstractThis article aims to analyze the role of pela gandong as local wisdom used as a cultural conflict resolution in the 1999-2002 Ambon conflict. Using sociology of conflict approach, the theory of cultural conflict resolution, and methods of collecting observational data and interviews with Ambonese Muslims and Christians, this paper finds that, first, ethnocentrism is the main cultural cause of the Ambon conflict, and, second, the Ambon conflict is resolved and peace is built firmly through the cultural conflict resolution of pela gandong. With noble values, especially brotherhood, equality, equality, togetherness and tolerance, pela gandong is very effective in resolving cultural conflicts both during the Ambon conflict, post-conflict and in fostering peace until now. During the Ambon conflict, there was no conflict between Muslim and Christian countries that were bound by pela gandong. After the conflict occurred, pela gandong became the foundation of cultural conflict resolution in rebuilding peace, strengthening the capacity of Ambonese people "from within"; rebuild their broken relationship; reaffirming the value of brotherhood among Maluku peoples; teach mutual recognition of religious and cultural differences; accelerate recovery from conflict trauma; re-knitting the greetings of fraternity; and building mutual trust between Muslim and Christian countries. Meanwhile, in the process of building peace up to now, Ambonese admit that pela gandong is effective in preventing “outsiders” who keep trying to reescalate the conflict, because every country in Ambon is already engaged in pela gandong one with another country.Keywords: pela gandong, religious cultural resolution, local wisdom. Artikel ini bertujuan untuk menganalisis peran pela gandong sebagai resolusi konflik kultural dalam konflik Ambon 1999-2002. Dengan menggunakan pendekatan sosiologi konflik, teori reolusi konflik kultural, serta metode pengumpulan data observasi dan wawancara dengan warga Ambon Muslim dan Kristen, tulisan ini menemukan bahwa, pertama, etnosentrisme merupakan penyebab kultural utama konflik Ambon, dan, kedua, konflik Ambon diselesaikan dan kedamaian terbangun kokoh melalui resolusi konflik kultural pela gandong. Dengan nilai-nilai luhur utamanya persaudaraan, persamaan, kesetaraan, kebersamaan dan toleransi, pela gandong sangat efektif menjadi resolusi konflik kultural baik selama konflik Ambon terjadi, paska konflik maupun dalam membina damai hingga kini. Selama konflik Ambon terjadi, tidak ditemukan adanya konflik antara negeri-negeri Muslim dan Kristen yang terikat pela gandong. Paska konflik terjadi, pela gandong menjadi fondasi resolusi konflik kultural dalam membangun kembali perdamaian, menguatkan kapasitas warga Ambon “dari dalam”; membangun kembali hubungan mereka yang sempat retak; menegaskan kembali nilai bersaudara sesama orang Maluku; mengajarkan saling mengakui perbedaan agama dan budaya; mempercepat pemulihan dari trauma konflik; merajut kembali persaudaraan salam sarane; dan membangun saling percaya antara negeri-negeri Muslim dan Kristen. Sedangkan dalam proses bina damai hingga kini, pela gandong juga diakui warga Ambon efektif menangkal “tangan-tangan luar” yang terus mencoba mengeskalasikan kembali konflik karena setiap negeri di Ambon sudah ber-pela gandong dengan satu negeri.